2017
DOI: 10.1101/238113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The individual functional connectome is unique and stable over months to years

Abstract: Using fMRI and functional connectivity analyses, it is possible to establish a functional connectome for an individual. The extent to which functional connectomes from adolescents and young adults remain identifiable across many years has not been investigated. Here we show in three publically available longitudinal resting-state fMRI datasets that connectome-based identification of adolescents and young adults scanned 1-3 years apart is possible at levels well above chance using whole-brain functional connect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 57 publications
11
79
2
Order By: Relevance
“…For example, Miranda‐Dominguez et al found that the unique connections in high‐order association regions in frontal and parietal cortices mainly contribute to the individual identification (Miranda‐Dominguez et al, ), and they further demonstrated that the high‐order systems, including the frontoparietal, dorsal attention, ventral attention, cingulo‐opercular and default systems, present substantial heritability variability (Miranda‐Dominguez et al, ). Horien et al found that both medial frontal and frontoparietal networks are unique and stable for individual identification during infancy (Horien et al, ). Finn et al found that the high‐order frontoparietal functional network, comprised of frontal, parietal and temporal lobes, is of the highest identification power (Finn et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Miranda‐Dominguez et al found that the unique connections in high‐order association regions in frontal and parietal cortices mainly contribute to the individual identification (Miranda‐Dominguez et al, ), and they further demonstrated that the high‐order systems, including the frontoparietal, dorsal attention, ventral attention, cingulo‐opercular and default systems, present substantial heritability variability (Miranda‐Dominguez et al, ). Horien et al found that both medial frontal and frontoparietal networks are unique and stable for individual identification during infancy (Horien et al, ). Finn et al found that the high‐order frontoparietal functional network, comprised of frontal, parietal and temporal lobes, is of the highest identification power (Finn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there has been a growing interest in the fingerprinting capability of the human brain, that is, whether the features of the human brain are unique and distinguishable for individual identification. Several studies performed individual identification based on structural or functional characteristics of the human brain, for example, morphological shape description of cortical and subcortical structures, named BrainPrint (Wachinger et al, ; Wachinger, Golland, & Reuter, ), shape description of white matter fibers, named FiberPrint (Kumar, Desrosiers, Siddiqi, Colliot, & Toews, ; Kumar, Toews, Chauvin, Colliot, & Desrosiers, ), and functional connectivity networks, named functional connectome fingerprint (Biazoli Jr et al, ; Finn et al, ; Horien, Shen, Scheinost, & Constable, ; Kaufmann et al, ; Liu et al, ; Tavor et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, there has been much recent interest in 'functional fingerprints'-that is, whether functional connectivity acts as a unique signature with which we can identify subjects. There have been several elegant demonstrations of this, suggesting that the functional information that we are able to capture with fMRI does indeed distinguish individuals 14 [Finn et al 2015;Horien et al 2018b]. However, we arguably already have a much more compelling way of fingerprinting subjects: structural data and the macro-anatomical folding patterns give a way to identify subjects that is simple, reliable and stable over decades.…”
Section: Understanding Spa Al Variabilitymentioning
confidence: 97%
“…With the development of personalized neuroscience, assessing the stability and reproducibility of brain profiles becomes a central issue. There is evidence that the individual connectome of the brain is as unique to the individual as their fingerprint (Finn et al, ; Horien, Shen, Scheinost, & Constable, ; Kong et al, ). However, these studies were mostly based on static functional connectivity (sFC), which assumes connections as spatially and temporally stationary over a measurement period.…”
Section: Introductionmentioning
confidence: 99%